PEMANFAATAN PATI JAHE MERAH (Zingiber Officinale Var Rubrum) SEBAGAI MODIFIKASI TEPUNG TERIGU DALAM PEMBUATAN KUE BAWANG DAN ANALISIS KANDUNGAN GIZINYA SERTA DAYA TERIMANYA OLEH MASYARAKAT - Ratih Lestari; Etti Sudaryati; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Food diversification is the governments effort to realize food security. Hence, as an effort to support the food diversification program, so did the utilization of red ginger starch is by product from making instant red ginger as modified of wheat flour in making onions chips. The type of research was an experiment conducted by completely randomized design. There were 2 treatment, the first treatment with composition red ginger starch 30%, cassava flour 20%, wheat flour 50% and second with composition the red ginger starch 50% and wheat flour 50%. Test acceptability onions chips done to 30 people the panel are student of public health faculty of Sumatera Utara University Medan, nutrient analysis was analyzed in the Laboratory of Industrial Research and Standarization Agency Medan. Data was analyzed by using Wilcoxon test . The results research showed that based on color , aroma , texture , and flavor, the onions chips that preferred is with the red ginger starch 30 % : cassava flour 20 % : wheat flour 50 % with  total score 311. Nutrition content onions chips is carbohydrates 46,9 % , proteins 4,38 % , fat 40,6 % , calcium 50,2 mg / kg , and iron 38 mg / kg . Red ginger starch onions chips it suggested can be consumed as a snack food or food variation for familly, school children, and teenagers. In addition can also be consumed by pregnant women and a person who often motion sickness experienced travel experienced travel to reduce a feeling of nausea . Keywords: Red Ginger Starch, Onions Chips, Acceptability, Nutrient Content